Integrasi Ma'ani Al-Hadis Yusuf Al-Qardhawi dan Cognitive Behaviour Therapy (CBT) dalam Penanganan Burnout dan Kecemasan: Analisis Terapeutik di Biro Psikologi Psikoprima - Nurul Arifin Nasution; Sulaiman Muhammad Amir (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to analyze the integration of Yusuf al-Qardhawi’s Ma‘ani al-Hadith approach with Cognitive Behaviour Therapy (CBT) in addressing burnout and anxiety and to formulate a Prophetic-CBT model. The study employed an interdisciplinary qualitative approach combining library and field research. The textual data consisted of hadiths concerning anxiety, sadness, weakness, laziness, anger, and psychological tranquility, which were analyzed using Yusuf al-Qardhawi’s principles of hadith interpretation. Field data were obtained through an in-depth interview with a clinical psychologist at Psikoprima Psychology Bureau and documentation of six cases, comprising four cases of anxiety and two cases of burnout. Data were analyzed through reduction, categorization, interpretation, and synthesis of the hadith findings with CBT techniques. The findings indicate a correspondence between prophetic coping principles in the hadiths and several CBT techniques, particularly cognitive restructuring, behavioral activation, emotion regulation, and relapse prevention. The concepts of al-hamm and al-hazan are relevant to understanding future-oriented anxiety and responses to past experiences, while al-‘ajz, al-kasal, and al-ghadab can be associated with problems of motivation, behavior, and emotional regulation. Based on this mapping, the study formulates Prophetic-CBT as an integrative model that combines CBT techniques with Islamic spiritual values. The model demonstrates potential as a culturally and religiously sensitive framework for Muslim clients, although its clinical effectiveness requires further investigation through quantitative studies and experimental designs